Lessons from SARS-CoV, MERS-CoV, and SARS-CoV-2 Infections: What We Know So Far - Radi Taha Alsafi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Within past decades, human infections with emerging and reemerging zoonotic viral pathogens have raised the eminent public health concern. Since November 2002, three highly pathogenic and major deadly human coronaviruses of the βετα-genera (β-hCoVs), namely, severe acute respiratory distress syndrome-coronavirus (SARS-CoV), middle east respiratory syndrome-coronavirus (MERS-CoV), and SARS-CoV-2, have been globally emerged and culminated in the occurrence of SARS epidemic, MERS outbreak, and coronavirus disease 19 (COVID-19) pandemic, respectively. The global emergence and spread of these three major deadly β-hCoVs have extremely dreadful impacts on human health and become an economic burden. Unfortunately, clear specific and highly efficient medical countermeasures for these three β-hCoVs and their underlying fatal illnesses remain under development. Although they belong to the same family and share many features and convergent evolution, these three deadly β-hCoVs have some important and obvious differences. By utilizing their lessons and gaining a deeper understanding of these β-hCoVs, we can identify areas of improvement and provide preparedness plans for fighting and controlling the future reemerging human infections that might arise from them or from other potential pathogenic hCoVs. Therefore, this review summarizes the state-of-the-art information and compares the similarities and dissimilarities between SARS-CoV, MERS-CoV, and SARS-CoV-2, in terms of their evolution trait, genome organization, host cell entry mechanisms, tissue infectivity tropisms, transmission routes and contagiousness, and the clinical characteristics, laboratory features, and immunological abnormalities of their related illnesses. It also provides an overview of the emerging SARS-CoV-2 variants. Additionally, it discusses the challenges of the most proposed treatment options for SARS-CoV-2 infections.